2014
DOI: 10.1371/journal.pone.0101808
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Endoplasmic Reticulum Stress and Unfolded Protein Response Associated Genes in Seed Stratification and Bud Endodormancy during Chilling Accumulation in Prunus persica

Abstract: Dormancy mechanisms in seeds and buds arrest growth until environmental conditions are optimal for development. A genotype-specific period of chilling is usually required to release dormancy, but the underlying molecular mechanisms are still not fully understood. To discover transcriptional pathways associated with dormancy release common to seed stratification and bud endodormancy, we explored the chilling-dependent expression of 11 genes involved in endoplasmic reticulum stress and the unfolded protein respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Two studies have examined parallel gene expression in stratifying seeds and chilling exposed buds and found a host of genes that have common expression patterns which support the hypothesis of common gene regulatory events during chilling accumulation (Leida et al 2012;Fu et al 2014). Leida et al (2012) examined the effect of different levels of stratification on expression of the 'dwarfing' growth inhibition phenotype in peach seeds and correlated this symptom with the expression of several genes also identified as differentially expressed during the endodormant to ecodormant transition in flower buds.…”
Section: What Evidence Is There That Bud Chilling Requirement and Seementioning
confidence: 93%
See 3 more Smart Citations
“…Two studies have examined parallel gene expression in stratifying seeds and chilling exposed buds and found a host of genes that have common expression patterns which support the hypothesis of common gene regulatory events during chilling accumulation (Leida et al 2012;Fu et al 2014). Leida et al (2012) examined the effect of different levels of stratification on expression of the 'dwarfing' growth inhibition phenotype in peach seeds and correlated this symptom with the expression of several genes also identified as differentially expressed during the endodormant to ecodormant transition in flower buds.…”
Section: What Evidence Is There That Bud Chilling Requirement and Seementioning
confidence: 93%
“…Another study has demonstrated the similarity in expression of genes between endodormant buds and seeds during chilling accumulation (Fu et al 2014). Fu et al (2014) propose a role for stress responsive endoplasmic reticulum genes during the accumulation of chilling and release from dormancy.…”
Section: What Evidence Is There That Bud Chilling Requirement and Seementioning
confidence: 99%
See 2 more Smart Citations
“…This was shown by chilling-induced expression of 11 genes involved in these processes (Fu et al, 2014). Ribosomes connect to the rough endoplasmic reticulum through a defined binding site (Bernabeau and Lake 1982) and are important in plant development.…”
Section: Biological Two-dimensional Quasicrystalsmentioning
confidence: 99%